PHOTOGRAPHY IN TOURISM - Anggara Putu Dharma Putra; Cokorda Istri Puspawati Nindhia (UHN IGB Sugriwa Denpasar, 2024)
Basically, humans are social creatures that cannot be separated from the people around them. This affects a person's lifestyle, be it a lifestyle that is closely related to the development of society, which contains values such as social strata, imagery, and self-actualization which are all for the search for a new identity. Where in this case we know that in the world of tourism has developed rapidly in which there are several components related to the world of tourism, one of which is media photography that plays a role in the world of tourism which is used to capture moments in us doing tourist trips, which in this case aims as a promotional media because of the results of good pictures will make people interested in visiting tourist attractions especially Bali, where we all know that Bali is one of the destinations visited by many local and foreign tourists, now this is how important media photography is in the world of tourism.